QUIZIZZ AS A HOTS-BASED ASSESSMENT MEDIA IN INCREASING STUDENTS' MOTIVATION - Roni Priyanda; Trisna Roy Pradipta; Rizki Amalia; Iden Rainal Ihsan; Priyanda R (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
This study describes the results of research on the implementation of the Quizizz application in learning with distance learning mode. It has three main objectives 1) to find out how to apply the Quizizz application as an assessment medium based on higher-order thinking skills; 2) the impact of the application of Quizizz as an assessment medium based on higher-order thinking skills on students' learning motivation; and 3) supporting and inhibiting factors for the implementation of Quizizz. This study used a qualitative descriptive approach and data were collected using observation, implementation, interviews, questionnaires, and documentation. The data analysis was carried out by grouping and presenting the data of 69 respondents and drawing conclusions. The use of Quizizz as an assessment medium based on HOT skills is carried out during daily tests, mid-semester, and end-semester tests. Based on the data, it was obtained information that the level of student learning motivation using Quizizz media based on higher-order thinking skills showed an average of 69.91. Furthermore, the supporting factor for the application of Quizizz media is that students are familiar with the use of Quizizz and the many tasks available on Quizizz. The inhibiting factor is that the internet connection at the student's residence still tends to be less supportive of online distance learning.